2018
DOI: 10.3390/rs10111768
|View full text |Cite
|
Sign up to set email alerts
|

Building Extraction in Very High Resolution Imagery by Dense-Attention Networks

Abstract: Building extraction from very high resolution (VHR) imagery plays an important role in urban planning, disaster management, navigation, updating geographic databases, and several other geospatial applications. Compared with the traditional building extraction approaches, deep learning networks have recently shown outstanding performance in this task by using both high-level and low-level feature maps. However, it is difficult to utilize different level features rationally with the present deep learning network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(68 citation statements)
references
References 45 publications
(59 reference statements)
0
61
0
Order By: Relevance
“…A trainable block, called the field-of-view (FoV), is proposed in [28] to boost the performance of the FCN. With the successful applications of U-Net in the pixel-wise area labellings, most current models [28][29][30][31][32][33] use encoder-decoder architectures. The mutation models enhance the buildings' semantic boundaries Remote Sens.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A trainable block, called the field-of-view (FoV), is proposed in [28] to boost the performance of the FCN. With the successful applications of U-Net in the pixel-wise area labellings, most current models [28][29][30][31][32][33] use encoder-decoder architectures. The mutation models enhance the buildings' semantic boundaries Remote Sens.…”
mentioning
confidence: 99%
“…2019, 11, 1897 3 of 23 by introducing a new loss or fusing features in more effective ways. Moreover, Yang et al [29] proposed an encoder-decoder network that was based on DenseNet and an attention mechanism, which is called the dense-attention network (DAN), which achieves remarkable improvements in building extraction. Meanwhile, Mou et al analyzed and encoded the long-range relationships in remote sensing images over sequences of time.…”
mentioning
confidence: 99%
“…By using dense connections, multiple level features are concatenated iteratively to form a dense block. It should be noted that we implemented the methods above (the training parameters for these methods are same as ours) and also incorporated some advanced numerical results on each of the three datasets reported in the literatures [52,66,67]. Figures 11-13 demonstrate the close-up views of the five classification results using three subset images of three test sets, respectively.…”
Section: Comparison With State-of-the-artmentioning
confidence: 99%
“…Subsequent studies [46][47][48][49] have demonstrated the performance of channel-wise attention mechanism in the semantic segmentation task. In remote sensing, some attempts [50][51][52] have been made to adopt attention mechanisms on the building extraction task. Yang et al [52] used a spatial attention module that weights map generated by applying sigmoid function at the deep features.…”
mentioning
confidence: 99%
“…The application scenario also extends from surface geographic objects to continuous phenomena such as highly dynamic clouds [45]. Some studies introduce the attention mechanism [46,47] to achieve an ideal segmentation effect by suppressing low-level features and noise through high-level features.…”
Section: Cnn Seriesmentioning
confidence: 99%